RS regenerating codes for cloud storage fault-tolerant system - Xi-ai YAN; Da-fang ZHANG; Jin-min YANG; Bo-yun ZHANG (Tongxin xuebao)
RS(Reed-Solomon) regenerating erasure codes was proposed for cloud storage fault-tolerant system,which not only inherited the reliability of the RS encoding,but also achieved the high efficiency of tolerance three faults.Hybrid recovery method of the single fault node based on RS regenerating erasure codes was introduced.And the theoretical lower bound of the number of accessing disks was computed.In theory,the performance evaluation of the storage overhead,decoding efficiency,and repair bandwidth of the RS regenerating erasure codes was carried out.Experiments results show that the repair performance of RS regenerating erasure codes is improved greatly than the similar erasure codes,and the total recovery time of the system is reduced by 20.8%~28.2% using hybrid recovery algorithm in the case of single fault.